Inequalities in untreated dental caries prevalence in preschool children in Brazil - Ardenghi, Thiago Machado; Piovesan, Chaiana; Antunes, Jose Leopoldo Ferreira (Revista de Saúde Pública, 2013)
OBJECTIVE: To evaluate the influence of social inequalities of individual and contextual nature on untreated dental caries in Brazilian children. METHODS: The data on the prevalence of dental caries were obtained from the Brazilian Oral Health Survey (SBBrasil 2010) Project, an epidemiological survey of oral health with a representative sample for the country and each of the geographical micro-regions. Children aged five (n = 7,217) in 177 municipalities were examined and their parents/guardians completed a questionnaire. Contextual characteristics referring to the municipalities in 2010 (mean income, fluorodized water and proportion of residences with water supply) were supplied by the Fundação Instituto Brasileiro de Geografia e Estatística (Brazilian Institute of Geography and Statistics). Multilevel Poisson regression analysis models were used to assess associations. RESULTS: The prevalence of non-treated dental caries was 48.2%; more than half of the sample had at least one deciduous tooth affected by dental caries. The index of dental caries in deciduous teeth was 2.41, with higher figures in the North and Northeast. Black and brown children and those from lower income families had a higher prevalence of untreated dental caries. With regards context, the mean income in the municipality and the addition of fluoride to the water supply were inversely associated with the prevalence of the outcome. CONCLUSIONS: Inequalities in the prevalence of untreated dental caries remain, affecting deciduous teeth of children in Brazil. Planning public policies to promote oral health should consider the effect of contextual factors as a determinant of individual risk.